CHALLENGING ROLES OF THE TEACHER IN INDONESIAN MODERN MIDDLE SCHOOLS - Wang, Gunawan (SEEIJ (Social Economics and Ecology International Journal), 2018)
Since year 2000, Indonesian ministry of education has allowed open curriculum system especially for adopting foreign curriculum system into national middle school system. As a result, there are demanding trends amongst parents and communities to reshape the role of teacher. The traditional instruction which emphasized the role of teacher as primarily source of knowledge is considered no longer effective to cope with latest trend of globalisation and internet technologies. For this reason, the article addressed the changing roles of modern teacher along with enhancing instructional activities. The article also examines the important trends that commonly ignored by the teachers such as: advance internet applications and characteristics of digital generation, and link them with variety of learningapproaches.